Surface morphology of fans in the high-Arctic periglacial environment of Svalbard : controls and processes. - de Haas, T.; Kleinhans, M.G.; Carbonneau, P.; Rubensdotter, L.; Hauber, E. (Earth-Science Reviews, 2015)
Fan-shaped landforms occur in all climatic regions on Earth. They have been extensively studied in many of these regions, but there are few studies on fans in periglacial, Arctic and Antarctic regions. Fans in such regions are exposed to many site-specific environmental conditions in addition to their geological and topographic setting: there can be continuous to discontinuous permafrost and snow avalanches and freeze–thaw cycles can be frequent. We study fans in the high-Arctic environment of Svalbard to (1) increase our fundamental knowledge on the morphology and morphometry of fans in periglacial environments, and (2) to identify the specific influence of periglacial conditions on fans in these environments. Snow avalanches have a large geomorphic effect on fans on Svalbard: the morphology of colluvial fans is mainly determined by frequent snow avalanches (e.g., flattened cross-profiles, exposed fine-grained talus on the proximal fan domain, debris horns and tails). As a result, there are only few fans with a rockfall-dominated morphology, in contrast to most other regions on Earth. Slush avalanches contribute significant amounts of sediment to the studied alluvial fans. The inactive surfaces of many alluvial fans are rapidly beveled and leveled by snow avalanches, solifluction and frost weathering. Additionally, periglacial reworking of the fan surface often modifies the original morphology of inactive fan surfaces, for example by the formation of ice-wedge polygons and hummocks. Permafrost lowers the precipitation threshold for debris-flow initiation, but limits debris-flow volumes. Global warming-induced permafrost degradation will likely increase debris-flow activity and -magnitude on fans in periglacial environments. Geomorphic activity on snow avalanche-dominated colluvial fans will probably increase due to future increases in precipitation, but depends locally on climate-induced changes in dominant wind direction.